Π‐Ruthenium Complexes of Hexaphyrins(1.1.1.1.1.1): A Triple‐Decker Complex Bearing Two Ruthenoarene Units. Issue 24 (8th May 2019) - Nakai, Akito; Ishida, Shin‐ichiro; Soya, Takanori; Osuka, Atsuhiro
Abstract: Ruthenium(II) π‐coordination onto [28]hexaphyrins(1.1.1.1.1.1) has been accomplished. Reactions of bis‐Au III and mono‐Au III complexes of hexakis(pentafluorophenyl) [28]hexaphyrin with [RuCl2 ( p ‐cymene)]2 in the presence of NaOAc gave the corresponding π‐ruthenium complexes, in which the [( p ‐cymene)Ru] II fragment sat on the deprotonated side pyrrole. A similar reaction of the bis‐Pd II [26]hexaphyrin complex afforded a triple‐decker complex, in which the two [( p ‐cymene)Ru] II fragments sat on both sides of the center of the [26]hexaphyrin framework. Abstract : Ruthenium(II) complexation of bis‐ and mono‐Au III [28]hexaphyrins afforded sandwich complexes with a ruthenoarene segment on the side pyrrole. On the other hand, Ru II complexation of bis‐Pd II [26]hexaphyrin afforded a triple‐decker complex bearing two ruthenoarene units on the two sides of the center of the [26]hexaphyrin framework.